Labour regulation in the on-demand economy: an ‘uberfication’ of the status quo? - Bruce, Caitlin (Department of Commercial Law, 2020)
Uber has reached rock-star status in the world of 'gigs’, 'rabbits’ and 'rides’ known as the 'on-demand economy’. Uber is but one in a sea of online platforms that seek to link clients with workers offering traditional services like transport, cleaning, repairs or running errands. These platforms act as a mediator between clients and workers and often set minimum quality standards, manage the payment process as well as the supply of work. However, as these platforms gain prevalence in today’s labour market, the question of worker protection comes rushing to the fore. On the one hand, these platforms are praised for having reduced the barriers to income for individuals who might not readily be able to enter the traditional labour market. On the other hand, critics of the on-demand economy argue that companies, like Uber, shift risks to their employees by misclassifying them as independent contractors, thereby weakening labour protections and driving down wages and in favour of their own profit margins. The question of whether Uber drivers are employees or independent contractors has sparked debate in the US. This study seeks to engage in this debate albeit in the South African context. In the absence of a definitive pronouncement from a South African decision maker as to the status of Uber drivers, the core research question posed by this study is whether Uber drivers are employees under South African law. The objective of the study is to determine whether existing labour laws in South Africa offer adequate protection to workers, like Uber drivers, in the on-demand economy. It will be argued that Uber drivers do not neatly fall within the definition of employee in section 213 of the LRA. However, Uber drivers do not neatly fit the category of independent contractor either. The fact that the aspects of the 'uberfied’ work relationship do not seem to speak to the factors enumerated in the South African tests of employment suggests that perhaps these factors are outdated in the context of the on-demand economy. But, this is not a new problem. It will be argued that the problems faced by 'gig’ workers in the on-demand economy should be viewed as an extension of a broader trend towards the casualisation of labour. In this sense, it can be said that the type of work relationship created by companies like Uber, is simply an 'uberfication’ of the status quo. In other words, companies like Uber have done no more than give the non-standard employee a smart phone application with which to earn an income.